Sheet and method for manufacturing a sheet

CN123022733APending Publication Date: 2026-10-30FUJIFILM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580022349.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-24
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0033]根据本发明,能够提供一种在热固性化合物的固化温度以上的温度下实施热压处理时能够形成导热性优异的导热性片材的片材及片材的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

Provided is a sheet and a method for manufacturing the sheet, which can form a thermally conductive sheet having excellent thermal conductivity when heat-pressing treatment is performed at a temperature equal to or higher than the curing temperature of a thermosetting compound. The sheet of the present invention is a sheet containing metal nanowires and a thermosetting compound, wherein the porosity of the sheet is 20.0% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a sheet material and a method for manufacturing the sheet material. Background Technology

[0002] The functionalization and miniaturization of electronic devices using semiconductor components are rapidly progressing. Along with this, the heat generated by the semiconductor components in these electronic devices is increasing, making it more necessary to dissipate this heat externally.

[0003] One method for releasing heat generated inside an electronic device to the outside is to connect the device to a cooling mechanism (e.g., a heat sink and a housing capable of introducing a refrigerant) via a thermally conductive sheet. For example, Patent Document 1 discloses a metal fiber sheet containing copper fibers, etc., as such a thermally conductive sheet.

[0004] Previous technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent No. 6678701 Summary of the Invention

[0007] The technical problem to be solved by the invention

[0008] As a method for manufacturing thermally conductive sheets, the following method is sometimes used: after obtaining a sheet by drying a composition containing a thermally conductive material, a thermosetting compound, and a solvent, hot pressing is performed at a temperature above the curing temperature of the thermosetting compound in order to cure the thermosetting compound contained in the sheet.

[0009] The inventors have clarified that after drying a composition comprising a thermosetting compound, a solvent, and a fibrous metal material as described in Patent Document 1 to obtain a sheet, hot pressing is performed at a temperature above the curing temperature of the thermosetting compound to obtain a thermally conductive sheet. As a result, the thermal conductivity of the thermally conductive sheet is sometimes insufficient, and there is room for improvement.

[0010] Therefore, the objective of this invention is to provide a sheet material and a method for manufacturing the sheet material that can be formed into a thermally conductive sheet material with excellent thermal conductivity when hot pressing is performed at a temperature above the curing temperature of a thermosetting compound.

[0011] means for solving technical problems

[0012] In order to solve the above-mentioned problems, the inventors conducted in-depth research and as a result, discovered that the above-mentioned problems can be solved by the following structure. [1]

[0014] A sheet comprising metal nanowires and a thermosetting compound, wherein, The porosity of the above-mentioned sheet is less than 20.0%. [2]

[0016] The sheet as described in [1], wherein, The oxidation rate of the aforementioned metal nanowires is less than 5.0%. [3]

[0018] The sheet as described in [1] or [2], wherein, The surface exposure rate of the aforementioned metal nanowires is above 20.0%. [4]

[0020] The sheet as described in any one of [1] to [3], wherein, The metal that makes up the above-mentioned metal nanowires is copper. [5]

[0022] The sheet as described in any one of [1] to [4], wherein, The content of the aforementioned metal nanowires is 30 to 80% of the total volume of the aforementioned sheet. [6]

[0024] The sheet as described in any one of [1] to [5], wherein, The thickness of the aforementioned sheet is 20–200 μm. [7]

[0026] The sheet as described in any one of [1] to [6], wherein, The aforementioned thermosetting compounds include epoxy compounds and phenolic compounds. [8]

[0028] The sheet as described in any one of [1] to [7], wherein, The molecular weight of the above thermosetting compounds is below 1000. [9]

[0030] A method for manufacturing a sheet includes a step of drying a composition comprising metal nanowires, a thermosetting compound and a solvent to obtain a sheet.

[0031] The viscosity of the above composition at 25°C is below 100 mPa·s. When the drying temperature of the above composition is set to T, the curing temperature of the above thermosetting compound is set to Tx, and the boiling point of the above solvent is set to Ty, If the difference between the above Tx and the above T is 10°C or more, The difference between the above Ty and the above T is above -60℃.

[0032] Invention Effects

[0033] According to the present invention, a sheet and a method for manufacturing the sheet are provided that can be formed into a thermally conductive sheet with excellent thermal conductivity when hot pressing is performed at a temperature above the curing temperature of the thermosetting compound. Attached Figure Description

[0034] Figure 1A This is a schematic cross-sectional view of a valve metal substrate before the anodizing process in an example of a method for manufacturing metal nanowires.

[0035] Figure 1B This is a schematic cross-sectional view of the structure after the anodizing process in an example of a method for manufacturing metal nanowires.

[0036] Figure 1C This is a schematic cross-sectional view of the structure after the metal filling process in an example of a method for manufacturing metal nanowires.

[0037] Figure 1D This is a schematic cross-sectional view of the structure after the separation process in an example of a method for manufacturing metal nanowires.

[0038] Figure 1E This is a schematic cross-sectional view of the structure (metal nanowire) after the crushing process in an example of a method for manufacturing metal nanowires. Detailed Implementation

[0039] The present invention will now be described in detail.

[0040] The following description of the constituent elements is sometimes based on representative embodiments of the present invention, but the present invention is not limited to such embodiments.

[0041] In this specification, the numerical range indicated by “~” refers to the range encompassed by the values ​​recorded before and after “~” as the lower and upper limits.

[0042] Furthermore, in this specification, when there are two or more components, the “content” of a component refers to the total content of these two or more components.

[0043] In this specification, within the numerical range described in stages, the upper or lower limit value recorded in a certain numerical range can be replaced with the upper or lower limit value of other numerical ranges described in stages. Furthermore, within the numerical range described in this specification, the upper or lower limit value recorded in a certain numerical range can be replaced with the value shown in the embodiment.

[0044] In this specification, a combination of two or more preferred methods is a more preferred method.

[0045] The term "process" in this specification refers not only to an independent process, but also to any process that achieves its intended purpose, even if it cannot be clearly distinguished from other processes.

[0046] Unless otherwise specified, the boiling point in this instruction manual refers to the boiling point at normal pressure (1 atmosphere, 760 mmHg).

[0047] [Sheet]

[0048] The sheet of the present invention (hereinafter also referred to as "the sheet") is a sheet containing metal nanowires and thermosetting compounds, and the porosity of the sheet is 20.0% or less.

[0049] The thermally conductive sheet obtained by hot-pressing the sheet at a temperature above the curing temperature of the thermosetting compound exhibits excellent thermal conductivity. While the detailed reasons for this are not explicitly stated, they can be roughly inferred as follows.

[0050] In other words, the pores in the sheet have low thermal conductivity, so a high porosity in the sheet leads to a decrease in the thermal conductivity of the resulting thermally conductive sheet. Furthermore, with high porosity, the contact area between the metal nanowires and the pores (air) increases, causing oxidation of the nanowire surfaces, which in turn reduces the thermal conductivity of the resulting sheet. Additionally, high porosity in the sheet results in insufficient fusion of the metal nanowires during hot pressing, further reducing the thermal conductivity of the resulting sheet.

[0051] Regarding this issue, it is believed that since the porosity of this sheet is below 20.0%, the aforementioned problem is unlikely to occur. Therefore, the thermally conductive sheet obtained after hot pressing becomes one with excellent thermal conductivity.

[0052] In addition, in this specification, when referred to simply as "hot pressing," unless otherwise specified, it means hot pressing performed at a temperature above the curing temperature of the thermosetting compound contained in the sheet.

[0053] The porosity of this sheet is 20.0% or less, and from the viewpoint of achieving better results in this invention, it is preferably 15.0% or less, more preferably 10.0% or less, and even more preferably 5.0% or less. The lower limit of the porosity of this sheet is 0%.

[0054] The porosity of this sheet refers to the ratio (%) of the area of ​​pores in the cross-section of this sheet to the total area of ​​the area outside the pores (i.e., the area of ​​the cross-section of this sheet).

[0055] Regarding porosity, the exposed cross-section obtained by cutting the sheet along its thickness direction is coated with platinum, then processed with focused ion beam (FIB), and the cross-section is photographed using a field emission scanning electron microscope (FE-SEM). The porosity is determined based on data obtained by image processing software (ImageJ). Specific measurement methods are described in the examples below.

[0056] From the viewpoint of achieving better results with the present invention, it is preferable that the thickness of the sheet is 20 to 200 μm, more preferably 50 to 170 μm, and even more preferably 80 to 120 μm.

[0057] Regarding the thickness of this sheet, the cross-section of the sheet was observed at any 10 points using a scanning electron microscope (SEM), and the thickness of each section was measured and calculated as the arithmetic mean.

[0058] The preferred state of this sheet is stage B. Stage B is described in JIS K6900:1944.

[0059] This sheet material is preferably used in the manufacture of thermally conductive sheets.

[0060] Thermally conductive sheets are used to directly or indirectly contact an object (e.g., a heat-generating body or a heat-absorbing body) and to effectively conduct heat from the object and release it to the outside.

[0061] Examples of objects that can be contacted include circuit boards, integrated circuits, power semiconductor circuits, heat sinks, lead frames, heat sinks, copper foils, and die-cutting bonding integrated films.

[0062] The thermally conductive sheet is preferably in state C. State C is described in JIS K6900:1944.

[0063] Thermally conductive sheets are obtained by hot-pressing the sheet at a temperature above the curing temperature of the thermosetting compound contained in the sheet (described later). There are no particular limitations on the hot-pressing method, and known methods can be used.

[0064] [Metal nanowires]

[0065] This sheet contains metallic nanowires.

[0066] "Metal nanowires" refer to conductive materials made of metal, in the shape of needles or filaments, and with a diameter of nanometers. Metal nanowires can be straight or curved. Furthermore, there are no particular limitations on the material of metal nanowires, as long as they contain metal; they can also contain components other than metal along with the metal. Metal nanowires can exist in this sheet as aggregates (metal nanowire aggregates).

[0067] In this invention, the metal constituting the above-mentioned metal nanowires is not particularly limited, but preferably has a resistivity of 10. 3 Materials with an Ω·cm or less, as specific examples, can preferably include gold (Au), silver (Ag), copper (Cu), aluminum (Al), titanium (Ti), nickel (Ni), and cobalt (Co).

[0068] From the viewpoint of thermal conductivity, Ag or Cu is preferred, and Cu is more preferred.

[0069] The diameter (arithmetic mean) of the above-mentioned metal nanowires is preferably 10-200 nm, more preferably 10-100 nm, and even more preferably 10-50 nm.

[0070] The length (arithmetic mean) of the above-mentioned metal nanowires is preferably 0.3 to 300 μm, more preferably 0.5 to 200 μm, and even more preferably 1 μm to 100 μm.

[0071] Here, the diameter and length of the aforementioned metal nanowires can be determined as follows: for example, by observing SEM images at magnification of 100 to 500x using a field emission scanning electron microscope (FE-SEM). Specifically, the diameter and length of the metal nanowires refer to the arithmetic mean of the diameter and length measurements of 10 randomly selected metal nanowires from SEM images taken at magnification of 100 to 500x, measured at 10 fields of view, for a total of 100 metal nanowires.

[0072] The length-to-diameter ratio (length / diameter) of the aforementioned metal nanowires (hereinafter also referred to as "aspect ratio") is preferably 10 or more, and more preferably 100 to 1000.

[0073] From the viewpoint of achieving better results with the present invention, the oxidation rate of the metal nanowires is preferably less than 7.0%, more preferably 5.0% or less, even more preferably 4.0% or less, particularly preferably 3.0% or less, and further preferably 2.0% or less, more preferably 1.0% or less. The lower limit of the oxidation rate of the metal nanowires is 0%.

[0074] The oxidation rate of the metal nanowires can be determined from a diffraction chart obtained by analyzing the surface of the sheet using an X-ray diffraction apparatus. Specifically, the percentage (%) of the peak area originating from the metal oxide relative to the peak area originating from the metal is determined from the diffraction chart, and this value is taken as the oxidation rate of the metal nanowires. Furthermore, specific measurement methods are described in the examples described later.

[0075] From the viewpoint of achieving better results from the present invention, it is preferable that the surface exposure rate of the metal nanowires is 15.0% or more, more preferably 20.0% or more, even more preferably 25.0% or more, and particularly preferably 30.0% or more.

[0076] From the viewpoint of adhesion, it is preferable that the surface exposure rate of the metal nanowires is 90% or less, more preferably 80% or less, and even more preferably 70% or less.

[0077] The surface exposure rate of metal nanowires refers to the ratio (%) of the area of ​​metal nanowires exposed on the surface of the sheet to the total area of ​​the portion other than the metal nanowires exposed on the surface of the sheet (i.e., the area of ​​the surface of the sheet).

[0078] Regarding the surface exposure rate of the metal nanowires, images of the surface of the sheet were taken under an optical microscope and magnified, and the result was determined based on data obtained by image processing software (ImageJ). Specific measurement methods are described in the examples described later.

[0079] The content of metal nanowires relative to the total volume of the sheet is preferably 30-80% by volume, more preferably 35-75% by volume, and even more preferably 40-70% by volume. The effect of the present invention is better when the content of metal nanowires is 30% by volume or more. Furthermore, when the content of metal nanowires is 80% by volume or less, the adhesion of the sheet to the object becomes good.

[0080] The content of metal nanowires can be determined based on the amount of metal nanowires used in the fabrication of this sheet, or it can be determined based on a cross-sectional image of this sheet.

[0081] Here, the method for determining the metal nanowire content (volume %) based on the amount of metal nanowires used in the manufacture of this sheet is as follows: Divide the weight of each component used in the manufacture of this sheet (solid component) by the theoretical specific gravity of each component to calculate the volume of each component (solid component) in this sheet. Then, divide the volume occupied by the metal nanowires by the sum of the volumes of all components (solid components) in this sheet, thereby obtaining the metal nanowire content (volume %).

[0082] Here, the method for determining the content of metal nanowires based on cross-sectional images of the sheet is as follows. A cross-section exposed by cutting the sheet along its thickness direction is captured using a scanning electron microscope (SEM), and the content is determined based on data obtained by image processing software (ImageJ). In this case, the content of metal nanowires is considered as a volume-based proportion (volume %), calculated as the percentage (%) of the area of ​​the metal nanowires in the cross-section of the sheet relative to the area of ​​the cross-section.

[0083] The content of metal nanowires relative to the total mass of the sheet is preferably 75-95% by mass, more preferably 80-95% by mass, and even more preferably 85-95% by mass. The effect of the present invention is better when the content of metal nanowires is 75% by mass or more. Furthermore, the strength of the sheet is better when the content of metal nanowires is 95% by mass or less.

[0084] <Metal Nanowire Manufacturing Methods>

[0085] As an example of a method for manufacturing metal nanowires, a method comprising the following steps can be listed: an anodizing step, forming a porous anodized film on the surface of a valve metal substrate; a metal filling step, filling the pores with metal; a separation step, separating the filled metal from the anodized film and the valve metal substrate; and a pulverizing step, pulverizing the separated metal (hereinafter also simply referred to as "separated metal") to obtain metal nanowires. When the metal nanowires obtained by this method are used in the manufacture of this sheet, the effects of the present invention are even more superior.

[0086] Next, use Figures 1A to 1E After providing an overview of each step in the manufacturing process of metal nanowires, a detailed explanation of each processing step is then provided.

[0087] like Figure 1A and Figure 1B As shown, in the anodizing process, the surface of the valve metal substrate 1 is anodized to form an anodized film 3 with porous (microporous) 2 on the surface of the valve metal substrate 1.

[0088] Next, as Figure 1C As shown, in the metal filling process, metal 4 is filled into the porous 2.

[0089] Next, as Figure 1D As shown, in the separation process, the filled metal 4 is separated from the anodic oxide film 3 and the valve metal substrate 1. Additionally, Figure 1D The manner shown represents the state of the separated metal 5 recovered through the separation process (the state in which a portion of the separated metal is condensed).

[0090] Next, as Figure 1E As shown, in the crushing process, metal nanowires 10 can be obtained by separating the metal 5 and crushing it.

[0091] (Valve metal substrate)

[0092] There are no particular limitations on the valve metal substrate used in the manufacturing method of metal nanowires, as long as it is a substrate containing valve metal.

[0093] Specifically, valve metals include, for example, aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, aluminum is preferred due to its good dimensional stability and relatively low price.

[0094] Therefore, in the manufacturing method of metal nanowires, it is preferable to use an aluminum-containing substrate (hereinafter referred to as "aluminum substrate") as the valve metal substrate.

[0095] There are no particular limitations on the aluminum substrate. Specific examples include: pure aluminum plates; alloy plates with aluminum as the main component and containing trace amounts of other elements; substrates on which high-purity aluminum is vapor-deposited onto low-purity aluminum (e.g., recycled materials); substrates on which high-purity aluminum is coated onto the surface of silicon wafers, quartz, and glass by methods such as vapor deposition and sputtering; and resin substrates obtained by laminating aluminum.

[0096] The purity of the valve metal on the surface of the valve metal substrate on the side subjected to anodizing treatment in the anodizing process described later is preferably 99.5% by mass or more, more preferably 99.9% by mass or more, and even more preferably 99.99% by mass or more. If the valve metal purity is within the above range, the regularity of the arrangement of the through-passage becomes sufficient.

[0097] Furthermore, it is preferable that the surface of the valve metal substrate on the side to be anodized in the anodizing process described later is subjected to heat treatment, degreasing treatment and mirror finishing treatment beforehand.

[0098] Here, the same treatments as those described in paragraphs

[0044] to

[0054] of Japanese Patent Application Publication No. 2008-270158 can be performed for heat treatment, degreasing treatment and mirror finishing treatment.

[0099] (Anodizing process)

[0100] The above-mentioned anodizing process is a process of forming a porous anodized film on the surface of the valve metal substrate by performing anodizing treatment on the surface of the valve metal substrate.

[0101] The anodizing process described above can be performed using conventionally known methods, but for the purpose of separating the filled metal with small diameter deviations in the separation process described later, it is preferable to use a self-ordering method or a constant voltage treatment.

[0102] Here, the self-ordering method or constant voltage treatment for anodizing can be implemented in accordance with the treatments described in paragraphs

[0056] to

[0108] and [Figure 3] of Japanese Patent Application Publication No. 2008-270158.

[0103] Anodizing can be achieved, for example, by using a solution with an acid concentration of 1 to 10% by mass to pass an electric current through the valve metal substrate as the anode.

[0104] The solution used for anodizing is preferably an acid solution, more preferably sulfuric acid, phosphoric acid, chromic acid, oxalic acid, sulfonamide acid, benzenesulfonic acid, aminosulfonic acid, glycolic acid, tartaric acid, malic acid, or citric acid, and even more preferably sulfuric acid, phosphoric acid, or oxalic acid, with oxalic acid being particularly preferred. These acids can be used alone or in combination of two or more.

[0105] The conditions for anodizing vary depending on the electrolyte used, and therefore cannot be determined uniformly. Generally, the preferred electrolyte concentrations are 0.1–20% by mass, the electrolyte temperature is -10–30°C, and the current density is 0.01–20 A / dm³. 2 The electrolyte concentration is 0.5–15% by mass, the electrolyte temperature is -5–25°C, and the current density is 0.05–15 A / dm³. The voltage ranges from 3 to 300 V, the electrolysis time is 0.5–30 hours, and more preferably, the electrolyte concentration is 0.5–15% by mass, the electrolyte temperature is -5–25°C, and the current density is 0.05–15 A / dm³. 2 The electrolyte concentration is 1-10% by mass, the liquid temperature is 0-20℃, and the current density is 0.1-10A / dm³. The electrolyte voltage ranges from 5 to 250V, the electrolysis time is 1-25 hours, and more preferably, the electrolyte concentration is 1-10% by mass, the liquid temperature is 0-20℃, and the current density is 0.1-10A / dm³. 2 Voltage 10-200V, electrolysis time 2-20 hours.

[0106] The processing time for anodizing is preferably 0.5 minutes to 16 hours, more preferably 1 minute to 12 hours, and even more preferably 2 minutes to 8 hours.

[0107] The thickness of the anodic oxide film formed by the above-described anodizing process is not particularly limited, but from the viewpoint of adjusting the length of the metal nanowires, it is preferably 0.3 to 300 μm, more preferably 0.5 to 120 μm, and even more preferably 0.5 to 100 μm.

[0108] In addition, regarding the thickness of the anodic oxide film, the anodic oxide film can be machined in the thickness direction using a focused ion beam (FIB), and its cross-section can be photographed using a field emission scanning electron microscope (FE-SEM) at a magnification of 50,000 times. The thickness can then be calculated as the average value of 10 points.

[0109] The density of the pores formed by the above anodizing process is not particularly limited, but is preferably 2 million / mm. 2 The above is preferred to be 10 million per mm. 2 The above is further optimized to 50 million / mm. 2 The above is particularly preferred, with 100 million pieces / mm. 2 above.

[0110] Furthermore, the density of the pores can be determined and calculated using the method described in paragraphs

[0168] and

[0169] of Japanese Patent Application Publication No. 2008-270158.

[0111] The average opening diameter of the pores formed by the above-mentioned anodizing process is not particularly limited, but from the viewpoint of adjusting the diameter of the metal nanowires, it is preferably 5 to 500 nm, more preferably 20 to 400 nm, even more preferably 40 to 200 nm, and particularly preferably 50 to 100 nm.

[0112] In addition, the average opening diameter of the pores can be calculated by taking surface photographs (magnification of 50,000) using FE-SEM, and using the average value measured at 50 points.

[0113] (Metal filling process)

[0114] The metal filling process described above is a process of filling the porous interior with metal after the anodizing process described above.

[0115] ·Metal

[0116] The metals mentioned above may be the same as those described as constituting the metal nanowires.

[0117] • Filling method

[0118] As a method for filling the aforementioned metal into the porous interior, for example, methods identical to those described in paragraphs

[0123] to

[0126] and [Figure 4] of Japanese Patent Application Publication No. 2008-270158 can be listed.

[0119] In the manufacturing method of metal nanowires, based on the reason that the metal nanowires produced are less likely to contain voids, it is preferable that the metal filling process includes a plating process.

[0120] Specifically, as a method for filling the porous interior with the aforementioned metal, an electroplating process is preferred, such as an electroplating method or an electroless plating method.

[0121] In conventional electroplating methods used for coloring, it is difficult to selectively deposit (grow) metal in pores with a high aspect ratio. This is believed to be because the deposited metal is consumed within the pores, and even with electrolysis for a certain period of time, the plating will not grow.

[0122] Therefore, in the manufacturing method of metal nanowires, when filling the metal by electroplating, a pause time needs to be set during pulse electrolysis or constant potential electrolysis. The pause time needs to be more than 10 seconds, preferably 30 to 60 seconds.

[0123] Furthermore, it is desirable to add ultrasound in order to promote the stirring of the electrolyte.

[0124] Furthermore, the electrolysis voltage is typically 20V or less, preferably 10V or less. It is preferable to pre-determine the deposition potential of the target metal in the electrolyte and perform constant-potential electrolysis within +1V of that potential. Additionally, when performing constant-potential electrolysis, it is preferable to use cyclic voltammetry, and constant-potential devices from companies such as Solartron, BAS, HOKUTO DENKO CORPORATION, and IVIUM can be used.

[0125] The plating solution can use plating solutions that are already known.

[0126] Specifically, when copper is deposited, an aqueous solution of copper sulfate is generally used, preferably with a concentration of 1–300 g / L, more preferably 100–200 g / L. Furthermore, adding hydrochloric acid to the electrolyte can promote deposition. In this case, a hydrochloric acid concentration of 10–20 g / L is preferred.

[0127] Furthermore, in the case of gold deposition, it is preferable to use a sulfuric acid solution of tetrachlorogold for electroplating by alternating current.

[0128] Furthermore, in electroless plating methods, it takes a long time to completely fill the pores composed of high aspect ratio pores with metal. Therefore, in the manufacturing method of metal nanowires, it is preferable to fill the metal by electroplating.

[0129] In the manufacturing method of metal nanowires, the preferred electroplating method is a process that sequentially combines alternating current electroplating and direct current electroplating.

[0130] In this alternating current electroplating method, for example, the voltage is modulated into a sinusoidal waveform at a predetermined frequency and applied. Furthermore, the waveform during voltage modulation is not limited to a sine wave; for example, it can also be a rectangular wave, a triangular wave, a sawtooth wave, or an anti-sawtooth wave.

[0131] Furthermore, the aforementioned processing methods can be appropriately used in DC electroplating.

[0132] In the manufacturing methods of metal nanowires, the rationale for shortening the manufacturing time is also... Figure 1C As shown, preferably, the metal filling process described above involves processing the entire area from the bottom of the pore to the opening, as well as the area from the bottom of the pore to the middle of the opening.

[0133] (Separation process)

[0134] The separation process described above is a process that separates the filled metal from the anodic oxide film and the valve metal substrate after the metal filling process described above.

[0135] Here, the method for separating the filled metal from the aforementioned anodic oxide film and the aforementioned valve metal substrate is not particularly limited, but methods that remove the aforementioned anodic oxide film and the aforementioned valve metal substrate (e.g., dissolution, peeling, etc.) and separate the filled metal can be preferably listed. Therefore, as a method after the aforementioned separation process, for example, a method in which the filled metal in the treatment liquid used in the dissolution process (dissolution treatment) described later is dispersed in a separated state can also be included.

[0136] In the method for manufacturing metal nanowires, there is no particular limitation on the method for removing the anodic oxide film and the valve metal substrate. For example, it can be removed by grinding. However, for the sake of making the length of the manufactured metal nanowires uniform, it is preferable that the separation process includes a dissolution process, that is, at least a portion of the anodic oxide film and the valve metal substrate is removed by dissolution treatment.

[0137] In the method for manufacturing metal nanowires, for the sake of maintaining the shape or size of the manufactured metal nanowires, it is preferable that the separation process includes a removal process in which the anodic oxide film is removed and the valve metal substrate is removed in one stage. More preferably, the removal of the anodic oxide film is a process in which the anodic oxide film is removed by a dissolution process.

[0138] Furthermore, for the same reason, the separation process described above can be a two-stage removal process that includes removing the valve metal substrate and then removing the anodic oxide film. In this case, it is more preferable that both stages of the removal process are removal processes performed by dissolution treatment.

[0139] • Removal of valve metal substrate

[0140] In the removal of the valve metal substrate, it is preferable to use a dissolution treatment solution that is not easy to dissolve the anodic oxide film but easy to dissolve the valve metal.

[0141] The dissolution rate of this treatment solution on the valve metal is preferably 1 μm / min or more, more preferably 3 μm / min or more, and even more preferably 5 μm / min or more. Similarly, the dissolution rate on the anodic oxide film is preferably 0.1 nm / min or less, more preferably 0.05 nm / min or less, and even more preferably 0.01 nm / min or less.

[0142] Specifically, the preferred treatment solution contains at least one metal compound with a lower ionization tendency than the valve metal and has a pH of 4 or less or 8 or more, more preferably a pH of 3 or less or 9 or more, and even more preferably a pH of 2 or less or 10 or more.

[0143] As such a treatment liquid, it is preferred to use an acid or alkaline aqueous solution as a matrix and, for example, to incorporate compounds of manganese, zinc, chromium, iron, cadmium, cobalt, nickel, tin, lead, antimony, bismuth, copper, mercury, silver, palladium, platinum, gold (e.g., chloroplatinic acid), their fluorides, and their chlorides.

[0144] The preferred matrix is ​​an acidic aqueous solution, and more preferably a mixed chloride.

[0145] In particular, from the viewpoint of handling tolerance, a treatment solution (hydrochloric acid / mercuric chloride) made by mixing mercuric chloride in an aqueous hydrochloric acid solution and a treatment solution (hydrochloric acid / copper chloride) made by mixing copper chloride in an aqueous hydrochloric acid solution are preferred.

[0146] Furthermore, the composition of this treatment solution is not particularly limited; for example, a bromine / methanol mixture, a bromine / ethanol mixture, aqua regia, etc., can be used.

[0147] Furthermore, the acid or alkali concentration of this treatment solution is preferably 0.01 to 10 mol / L, more preferably 0.05 to 5 mol / L.

[0148] Furthermore, the preferred processing temperature using this treatment solution is -10°C to 80°C, and more preferably 0°C to 60°C.

[0149] Furthermore, the removal of the valve metal substrate is performed by contacting the valve metal substrate after the metal filling process with the aforementioned treatment liquid. The contact method is not particularly limited; examples include immersion and spraying. Immersion is preferred. The contact time is preferably 10 seconds to 5 hours, more preferably 1 minute to 3 hours.

[0150] • Removal of anodic oxide film

[0151] In the removal of the anodic oxide film described above, a solvent that selectively dissolves the anodic oxide film but does not dissolve the metal filling the pores can be used, and either an alkaline aqueous solution or an acidic aqueous solution can be used.

[0152] When using an alkaline aqueous solution, it is preferable to use an aqueous solution of at least one alkali selected from the group consisting of sodium hydroxide, potassium hydroxide, and lithium hydroxide, and more preferably an aqueous solution of potassium hydroxide. Furthermore, the concentration of the alkaline aqueous solution is preferably 1 to 30% by mass. The temperature of the alkaline aqueous solution is preferably 10 to 60°C, more preferably 20 to 60°C, and even more preferably 30 to 60°C.

[0153] On the other hand, when using an aqueous acid solution, it is preferable to use an aqueous solution of inorganic acids such as chromic acid, sulfuric acid, phosphoric acid, nitric acid, hydrochloric acid, and oxalic acid, or a mixture thereof, and more preferably an aqueous solution of chromic acid. Furthermore, the concentration of the aqueous acid solution is preferably 1 to 30% by mass. The temperature of the aqueous acid solution is preferably 15 to 80°C, more preferably 20 to 60°C, and even more preferably 30 to 50°C.

[0154] Furthermore, the removal of the aforementioned anodic oxide film is performed by contacting the aforementioned alkaline aqueous solution and acidic aqueous solution after the aforementioned metal filling process (preferably after removing the valve metal substrate). The contact method is not particularly limited; for example, immersion and spraying methods can be used. Immersion is preferred. The immersion time in the alkaline and acidic aqueous solutions is preferably 1 to 120 minutes, more preferably 2 to 90 minutes, further preferably 3 to 60 minutes, and particularly preferably 3 to 30 minutes. Preferably, it is 3 to 20 minutes, more preferably 3 to 10 minutes.

[0155] (Grinding process)

[0156] The above-mentioned crushing process is a process of crushing and separating metals after the above-mentioned separation process.

[0157] There are no particular limitations on the method of crushing and separating metals, but, for example, a method of crushing the metals by impact in a liquid can be preferably listed.

[0158] The liquid (solvent) used in the pulverization process is not particularly limited as long as it does not cause the separated metals to deteriorate or dissolve. Examples include water, ethanol, methanol, acetone, methyl ethyl ketone, butanol, ethyl acetate, butyl acetate, tetrahydrofuran, toluene, dimethylformamide, cyclohexane, and cyclohexanone. Among these, water is preferred from a safety point of view.

[0159] Furthermore, from the viewpoint of being able to produce metal nanowires with higher bonding strength during bonding, it is preferable to carry out the above-mentioned pulverization process in water or an aqueous solution with a concentration of alkali or acid of less than 1% by mass.

[0160] Examples of pulverization processes include cavitation pulverization and ceramic ball collision pulverization, which can be performed using devices such as ultrasonic cleaners, ultrasonic homogenizers, jet mills, and wet micronization devices. Among these, cavitation pulverization or ceramic ball collision pulverization is preferred, and cavitation pulverization is more preferred.

[0161] In this invention, from the perspective of making the processing more uniform and improving productivity, it is preferable that the concentration of the separated metal in the liquid at the time of crushing pressure in the liquid is 0.1 to 50 by mass.

[0162] Furthermore, based on the reason that metal nanowires with higher bonding strength can be obtained during bonding, it is more preferable that the concentration of the separated metal in the liquid at the crushing pressure in the liquid is 0.5 to 30% by mass, and even more preferably 1 to 10% by mass.

[0163] (Drying process)

[0164] The preferred method for manufacturing metal nanowires includes a drying step between the separation step and the pulverization step to further dry the separated metal.

[0165] Here, there is no particular limitation on the method of drying and separating the metal. After removing the above-mentioned anodic oxide film and valve metal substrate, separation operations such as filtration and centrifugation using filters are performed, thereby enabling the drying by recovering the separated metal.

[0166] (Protective layer formation process)

[0167] Based on the reason that it can reduce the oxidation rate of metal nanowires, the method for manufacturing metal nanowires preferably includes, after the above separation step (or after the above drying step if the above drying step is included), a step of forming a protective layer on the separated metal (metal nanowires) using at least one selected from the group including corrosion inhibitors and silane coupling agents.

[0168] The protective layer formation process is preferably performed after the "reduction or removal process" described later.

[0169] Corrosion inhibitor

[0170] The above-mentioned corrosion inhibitors are not particularly limited and can be any known corrosion inhibitors.

[0171] As corrosion inhibitors, examples include compounds containing at least one of nitrogen, oxygen, and sulfur atoms.

[0172] From a durability point of view, the corrosion inhibitor is preferably a heterocyclic compound containing at least one nitrogen atom and one oxygen atom, more preferably a compound containing a five-membered ring structure containing one or more nitrogen atoms, and particularly preferably a compound selected from at least one compound from the group consisting of compounds containing an imidazole structure, compounds containing a triazole structure, compounds containing a tetraazole structure, compounds containing a benzimidazole structure, and compounds containing a thiadiazole structure. The five-membered ring structure containing one or more nitrogen atoms can be a monocyclic structure or a partial structure constituting a condensation ring.

[0173] Furthermore, based on the reason that it is easy to adsorb onto the surface of the separated metal, the corrosion inhibitor is preferably a compound containing at least one of an acid containing a polar group and a base containing a polar group.

[0174] Polar groups, which are present in acids and bases containing polar groups, can be exemplified by carboxyl groups, sulfonic acid groups, phosphonic acid groups, phosphate groups, primary to quaternary ammonium salt groups, carboxyl groups, sulfonate groups, phosphonate groups, and phosphate groups.

[0175] Furthermore, based on the reason that it bonds with metal ions to form fault ions and becomes easier to protect the surface of the separated metal, the corrosion inhibitor is preferably a compound containing a carboxyl group.

[0176] Specific examples of the aforementioned corrosion inhibitors include imidazole, benzimidazole, 1,2,4-triazole, benzotriazole (BTA), tolyltriazole (TTA), butylbenzyltriazole, alkyl dithiothiadiazole, alkyl thiol, 2-aminopyrimidine, 5,6-dimethylbenzimidazole, 2-amino-5-mercapto-1,3,4-thiadiazole, 2,5-dimercapto-1,3,4-thiadiazole (DMTDA), 2-mercaptopyrimidine, 2-mercaptobenzoxazole, 2-mercaptobenzothiazole (MBT), and 2-mercaptobenzimidazole.

[0177] Other specific examples of the aforementioned corrosion inhibitors include aliphatic carboxylic acids such as acetic acid, propionic acid, palmitic acid, stearic acid, lauric acid, arachidic acid, terephthalic acid, and oleic acid; carboxylic acids such as glycolic acid, lactic acid, oxalic acid, malic acid, tartaric acid, and citric acid; amino polycarboxylic acids such as ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), iminodiacetic acid (IDA), ethylenediaminediacetic acid (EDDA), and ethylene glycol diethyl ether diaminetetraacetic acid (GEDA); uric acid; gallic acid; and thiourea.

[0178] Corrosion inhibitors can be used alone or in combination of two or more.

[0179] Furthermore, based on the reason that the corrosion inhibitor has good stability over time, it is preferable that the corrosion inhibitor contains a compound containing nitrogen atoms (nitrogen-containing compound), more preferably a nitrogen-containing compound, and even more preferably a heterocyclic compound containing at least one of nitrogen atoms and sulfur atoms.

[0180] From the viewpoint of achieving better results from the present invention, it is preferred that the corrosion inhibitor be at least one selected from the group consisting of compounds containing an imidazole structure, compounds containing a triazole structure, compounds containing a tetraazole structure, and thiourea.

[0181] ·Silane coupling agent

[0182] As a silane coupling agent, there are no particular limitations, and examples include dimethyldimethoxysilane, dimethyldiethoxysilane, methylethyldimethoxysilane, methylethyldiethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, decyltrimethoxysilane, phenyltriethoxysilane, p-styryltrimethoxysilane, vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, 2-methylpropane... Acryloyloxypropyltrimethoxysilane, 3-acryloyloxypropyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-(3,4-epoxycyclohexyl), N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanate propyltriethoxysilane, 3-ureidopropyltrialkoxysilane, tri-(trimethoxysilylpropyl)isocyanurate and methyltriisocyanate silane, etc.

[0183] Silane coupling agents can be used alone or in combination with two or more.

[0184] From the viewpoint that it can further reduce the oxidation rate of metal nanowires, silane coupling agents with epoxy groups are preferred as silane coupling agents.

[0185] Commercially available products can be used as silane coupling agents, such as KA-1003, KBM-1003, KBE-1003, KBM-303, KBM-402, KBM-403, KBE-402, KBE-403, KBM-1403, KBM-502, KBM-503, KBE-502, KBE-503, KBM-5103, KBM-602, KBM-603, KBE-603, KBM-903, KBE-903, K... BE-9103, KBM-573, KBM-575, KBM-6123, KBE-585, KBM-703, KBM-802, KBM-803, KBE-846, KBE-9007, KBM-04, KBE-04, KBM-13, KBE-13, KBE-22, KBE-103, HMDS-3, KBM-3063, KBM-3103C, KPN-3504, and KF-99 (all manufactured by Shin-Etsu Chemical Co., Ltd.).

[0186] There is no particular limitation on the method for forming such a protective layer. For example, the following methods can be listed: adding the separated metal recovered in the above-mentioned drying process to an aqueous solution containing a corrosion inhibitor and / or a silane coupling agent and stirring; adding a corrosion inhibitor and / or a silane coupling agent to a cleaning solvent for cleaning the separated metal recovered in the above-mentioned drying process; and using a composition containing at least one of the group including corrosion inhibitors and silane coupling agents in the manufacture of this sheet (refer to the sheet manufacturing method described below).

[0187] (Reduction or removal process)

[0188] From the viewpoint of reducing the oxidation rate of the metal nanowires contained in the sheet, the method for manufacturing metal nanowires further includes a step of reducing or removing the surface oxide layer of the separated metal (metal nanowires) between the separation step and the pulverization step (preferably before the drying step if the drying step is included).

[0189] As a reduction or removal process, examples include the immersion treatment using alkaline and acidic aqueous solutions described in the above-described removal process of the anodic oxide film.

[0190] Furthermore, in addition to the acid solutions listed in the above-described anodic oxide film removal process, citric acid aqueous solution may also be used as the acid solution used in this process.

[0191] [Thermosetting compounds]

[0192] This sheet contains thermosetting compounds.

[0193] Thermosetting compounds are compounds that begin to cure upon heating above a curing temperature, and preferably have curable groups. Examples of curable groups include epoxy groups (oxocyclopropyl) and active hydrogen groups (described later).

[0194] Thermosetting compounds can be any of polymers and monomers.

[0195] From the viewpoint of achieving better results with the present invention, it is preferable that the molecular weight of the thermosetting compound is 1000 or less, more preferably 750 or less, and even more preferably 500 or less.

[0196] From the viewpoint of viscosity, it is preferable that the lower limit of the molecular weight of the thermosetting compound is 100 or more, more preferably 150 or more, and even more preferably 200 or more.

[0197] Furthermore, when using two or more thermosetting compounds, from the viewpoint of achieving better results according to the present invention, it is preferable that the molecular weight of all types of thermosetting compounds satisfies the above-mentioned value.

[0198] Examples of thermosetting compounds include epoxy compounds, cyclobutane compounds, acrylic acid compounds, methacrylic acid compounds, benzoguanidine compounds, rosin-modified maleic acid compounds, rosin-modified fumaric acid compounds, melamine compounds, urea compounds, and compounds containing active hydrogen groups. A thermosetting compound may contain only one type or two or more types.

[0199] From the viewpoint of achieving better results according to the present invention, the thermosetting compound includes at least one selected from the group consisting of epoxy compounds and compounds containing active hydrogen groups (e.g., phenolic compounds), more preferably including both epoxy compounds and phenolic compounds.

[0200] The curing temperature of the thermosetting compound (corresponding to the curing temperature Tx described later) is preferably 80–220°C, more preferably 100–200°C, and even more preferably 120–180°C. Here, the curing temperature of the thermosetting compound is the temperature at which the curing of the thermosetting compound begins, specifically, it refers to the temperature at which the heat peak rises due to curing in the differential scanning calorimetry (DSC) analysis of the thermosetting compound.

[0201] The content of the thermosetting compound relative to the total mass of the sheet is preferably 5 to 25% by mass, more preferably 5 to 20% by mass, and even more preferably 5 to 15% by mass. The sheet exhibits superior strength when the content of the thermosetting compound is 5% by mass or more. Furthermore, the invention is more effective when the content of the thermosetting compound is 25% by mass or less.

[0202] In addition, the content (mass%) of thermosetting compounds on a mass basis is shown, but the content (volume%) of thermosetting compounds on a volume basis can be calculated as follows: Divide the loading weight (solid component) of each component used in manufacturing this sheet by the theoretical specific gravity of each component to obtain the volume of each component (solid component) in this sheet. Then, divide the volume occupied by the thermosetting compound by the sum of the volumes of each component (solid component) in this sheet, thereby obtaining the content (volume%) of the thermosetting compound.

[0203] <Epoxy Compounds>

[0204] Epoxy compounds are compounds having one or more epoxy groups. However, in this specification, compounds having silyl groups and epoxy groups are not classified as epoxy compounds, but as the aforementioned silane coupling agents.

[0205] An epoxy group is a group formed by removing one or more hydrogen atoms (preferably one hydrogen atom) from an ethylene oxide ring. Where possible, the epoxy group may further have substituents. Examples of substituents include linear or branched alkyl groups having 1 to 5 carbon atoms and aromatic cyclic groups.

[0206] The number of epoxy groups in the epoxy compound is preferably 2 or more, more preferably 2 to 40, even more preferably 2 to 10, and particularly preferably 2.

[0207] Epoxy compounds can be either liquid crystal or non-liquid crystal.

[0208] In other words, epoxy compounds can be liquid crystal compounds with epoxy groups.

[0209] The epoxy compound is preferably a polyhydroxy aromatic ring type glycidyl ether (polyhydroxy aromatic ring type epoxy compound).

[0210] The polyhydroxy aromatic ring type glycidyl ether is a compound having a structure formed by glycidylating two or more of the above-mentioned hydroxyl groups in an aromatic ring having 2 or more (preferably 2 to 6, more preferably 2 or 3, and even more preferably 2) hydroxyl groups as substituents.

[0211] The aromatic ring can be any of an aromatic hydrocarbon ring or an aromatic heterocycle, preferably an aromatic hydrocarbon ring.

[0212] The aromatic ring described above can be either monocyclic or polycyclic. The number of ring members in the aromatic ring is preferably 5 to 15, more preferably 6 to 12, and even more preferably 6. The aromatic ring may have substituents other than a hydroxyl group.

[0213] Examples of glycidyl ethers of the polyhydroxy aromatic ring type mentioned above include 1,3-phenylenebis(glycidyl ether).

[0214] Examples of epoxy compounds include compounds with a partially rod-like structure (rod-like compounds) and compounds with a partially disc-like structure (disc-like compounds).

[0215] Commercially available epoxy compounds can be used, such as EPICLON (registered trademark) EXA-830CRP, EXA-830LVP, EXA-835LV (all product names manufactured by DIC Corporation), etc., which are bisphenol F type epoxy compounds.

[0216] Epoxy compounds can be used alone or in combination with two or more.

[0217] From the viewpoint of achieving better results with the present invention, it is preferable that the molecular weight of the epoxide compound is 1000 or less, more preferably 750 or less, and even more preferably 500 or less.

[0218] From the viewpoint of viscosity, it is preferable that the lower limit of the molecular weight of the epoxy compound is 100 or more, more preferably 150 or more, and even more preferably 200 or more.

[0219] The epoxy equivalent of the epoxy compound is preferably 100 to 250 g / eq, more preferably 120 to 220 g / eq, and even more preferably 140 to 190 g / eq. Furthermore, the epoxy equivalent is the mass of the epoxy compound per equivalent of epoxy groups, which can be determined according to JIS K7236 (2009).

[0220] The epoxy compound content relative to the total mass of the sheet is preferably 3 to 17% by mass, more preferably 3 to 13% by mass, and even more preferably 3 to 10% by mass. The sheet exhibits superior strength when the epoxy compound content is 3% by mass or more. Furthermore, the invention is more effective when the epoxy compound content is 17% by mass or less.

[0221] <Compounds containing active hydrogen groups>

[0222] The compound containing an active hydrogen group is a compound having 1 or more (preferably 2 or more, more preferably 2 to 10) active hydrogen groups (active hydrogen groups).

[0223] Examples of active hydrogen groups include hydroxyl, primary amine, secondary amine, and thiol groups, with hydroxyl being the most preferred.

[0224] The compound containing an active hydrogen group is a polyol having 2 or more (preferably 3 or more, more preferably 3 to 6) hydroxyl groups.

[0225] When the sheet material contains epoxy compounds and compounds containing active hydrogen groups, phenolic compounds are preferred as compounds containing active hydrogen groups.

[0226] Phenolic compounds are compounds having 1 or more phenolic hydroxyl groups (preferably 2 or more, more preferably 3 or more, and even more preferably 3 to 6).

[0227] Phenolic compounds preferably have a triazine skeleton.

[0228] The term "having a triazine skeleton" in phenolic compounds refers to the presence of 1 or more (preferably 1 to 5) triazine cyclic groups in the phenolic compound.

[0229] Examples of compounds containing active hydrogen groups include benzene polyols such as pyrogallol, biphenyl aryl phenolic resins, phenolic varnish resins, cresol phenolic varnish resins, aromatic hydrocarbon formaldehyde resin modified phenolic resins, dicyclopentadienol addition-type resins, phenolic aryl alkyl resins, polyphenolic varnish resins synthesized from polyvalent hydroxyl compounds and formaldehyde, naphthol aryl alkyl resins, trimethylolmethane resins, tetraphenol ethane resins, naphthol phenolic varnish resins, naphthol-phenol cocondensed phenolic varnish resins, naphthol-cresol cocondensed phenolic varnish resins, biphenyl-modified phenolic resins, biphenyl-modified naphthol phenolic resins, aminotriazine-modified phenolic resins, and alkoxy-containing aromatic ring-modified phenolic varnish resins.

[0230] Compounds containing active hydrogen groups can be commercially available, such as BIR-PC (a phenolic compound manufactured by ASAHI ORGANICCHEMICALS INDUSTRY CO.,LTD) and phenolic resins manufactured by Sumitomo Bakelite Co., Ltd.

[0231] Compounds containing active hydrogen groups can be used alone or in combination with two or more.

[0232] The content of hydroxyl groups in compounds containing active hydrogen groups is preferably 3.0 mmol / g or more, more preferably 4.0 mmol / g or more. The upper limit is preferably 25.0 mmol / g or less, more preferably 20.0 mmol / g or less. The above-mentioned hydroxyl group content refers to the number of moles of hydroxyl groups (preferably phenolic hydroxyl groups) present in 1 g of the compound containing active hydrogen groups.

[0233] Furthermore, compounds containing active hydrogen groups, in addition to hydroxyl groups, may also have groups containing active hydrogen groups (e.g., carboxyl groups) that can undergo polymerization reactions with epoxides.

[0234] The content of active hydrogen (the total content of hydrogen atoms in hydroxyl and carboxyl groups, etc.) in compounds containing active hydrogen groups is preferably 3.0 mmol / g or more, more preferably 4.0 mmol / g or more. The upper limit is preferably 25.0 mmol / g or less, more preferably 20.0 mmol / g or less. The above-mentioned content of active hydrogen refers to the number of moles of active hydrogen atoms per gram of the compound containing active hydrogen groups.

[0235] From the viewpoint of achieving better results with the present invention, it is preferable that the molecular weight of the compound containing an active hydrogen group (preferably a phenolic compound) is 1000 or less, more preferably 750 or less, and even more preferably 500 or less.

[0236] From the viewpoint of viscosity, it is preferable that the molecular weight of the compound containing active hydrogen groups (preferably a phenolic compound) is at least 100, more preferably 150 or more, and even more preferably 200 or more.

[0237] The content of compounds containing active hydrogen groups (preferably phenolic compounds) relative to the total mass of the sheet is preferably 2 to 8% by mass, more preferably 2 to 7% by mass, and even more preferably 2 to 5% by mass. The sheet exhibits superior strength when the content of compounds containing active hydrogen groups is 2% by mass or more. Furthermore, the present invention is more effective when the content of compounds containing active hydrogen groups is 8% by mass or less.

[0238] When the thermosetting compound includes an epoxy compound and a compound containing active hydrogen groups (preferably a phenolic compound), it is preferable that the epoxy compound and the compound containing active hydrogen groups are contained in the sheet in such a manner that the epoxy groups of the epoxy compound and the active hydrogen groups of the compound containing active hydrogen groups react in equivalent amounts. For example, when the number of epoxy groups in the epoxy compound is 2 and the number of active hydrogen groups in the compound containing active hydrogen groups is 5, it is preferable that the epoxy compound and the compound containing active hydrogen groups are contained in the sheet in a molar ratio of epoxy compound: active hydrogen group = 5:2.

[0239] When the thermosetting compound includes an epoxy compound and a compound containing an active hydrogen group (preferably a phenolic compound), the total content of the epoxy compound and the compound containing an active hydrogen group is preferably 20 to 100% by mass relative to the total mass of the thermosetting compound, more preferably 60 to 100% by mass, and even more preferably 90 to 100% by mass.

[0240] [Other ingredients]

[0241] This sheet material may contain components other than those described above (hereinafter also referred to as "other components"). Specific examples of other components include various components, their decomposition products, and their reactants that may be contained in the composition described below. Other components may be used alone or in combination of two or more.

[0242] [Sheet manufacturing method]

[0243] The method for manufacturing the sheet of the present invention (hereinafter also referred to as "the manufacturing method") includes a step (hereinafter also referred to as "the drying step") of drying a composition comprising metal nanowires, a thermosetting compound, and a solvent (hereinafter also referred to as "the composition") to obtain the sheet. The viscosity of this composition at 25°C is below 100 mPa·s. When the drying temperature of the above composition is set to T, the curing temperature of the above thermosetting compound is set to Tx, and the boiling point of the above solvent is set to Ty, the difference between Tx and T is 10°C or more, and the difference between Ty and T is -60°C or more.

[0244] This manufacturing method is an example of a preferred embodiment of the method for manufacturing the aforementioned sheet material. According to this manufacturing method, the aforementioned sheet material can be readily obtained.

[0245] [This composition]

[0246] The composition comprises metal nanowires, a thermosetting compound, and a solvent, and preferably further comprises at least one selected from the group consisting of corrosion inhibitors and silane coupling agents.

[0247] <Metal Nanowires>

[0248] The metal nanowires contained in this composition are the same as those contained in the sheet described above, including preferred embodiments. From the viewpoint of readily obtaining the sheet, it is preferable that the metal nanowires contained in this composition are metal nanowires obtained by performing the aforementioned "reduction or removal process".

[0249] The content (mass%) of metal nanowires relative to the total solid content of the composition also includes, preferably, the content (mass%) of metal nanowires relative to the total mass of the sheet.

[0250] <Thermosetting compounds>

[0251] The thermosetting compounds contained in this composition also include, preferably, the same thermosetting compounds contained in the sheet described above.

[0252] The content (mass%) of thermosetting compounds relative to the total solid content of the composition also includes, preferably, the content (mass%) of thermosetting compounds relative to the total mass of the sheet.

[0253] <Solvent>

[0254] The solvent contained in this composition is preferably an organic solvent.

[0255] The boiling point of the solvent (corresponding to the boiling point Ty described later) is preferably 130°C or lower, more preferably 100°C or lower, and even more preferably 80°C or lower. As long as the boiling point of the solvent is 130°C or lower, the thermal curing of thermosetting compounds in the film during the drying process can be suppressed, and the formation of pores in the sheet can be suppressed.

[0256] From the viewpoint of preventing volatilization except during heating, it is preferable that the lower limit of the boiling point of the solvent (corresponding to the boiling point Ty described later) is 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher.

[0257] Specific examples of organic solvents include cyclohexanone (boiling point 156°C), ethyl acetate (boiling point 77.1°C), methyl ethyl ketone (boiling point 79.64°C), dichloromethane (boiling point 39.6°C), and tetrahydrofuran (boiling point 66°C). From the viewpoint of suppressing the thermal curing of thermosetting compounds in the film during the drying process and suppressing the formation of pores in the sheet, methyl ethyl ketone and ethyl acetate are preferred, and methyl ethyl ketone is more preferred.

[0258] Solvents can be used alone or in combination of two or more.

[0259] <Corrosion Inhibitors and Silane Coupling Agents>

[0260] From the viewpoint of being able to further reduce the oxidation rate of the metal nanowires contained in the sheet, it is preferable that the composition contains at least one selected from the group including corrosion inhibitors and silane coupling agents.

[0261] The corrosion inhibitors and silane coupling agents also include, preferably, the same corrosion inhibitors and silane coupling agents listed in the protective layer formation step of the above-described method for manufacturing metal nanowires.

[0262] When the composition contains a corrosion inhibitor, the corrosion inhibitor content is preferably 0.01 to 10% by mass relative to the total mass of the composition, more preferably 0.05 to 5% by mass, and even more preferably 0.1 to 1% by mass.

[0263] When the composition contains a silane coupling agent, the content of the silane coupling agent is preferably 0.01 to 10% by mass relative to the total mass of the composition, more preferably 0.05 to 5% by mass, and even more preferably 0.1 to 1% by mass.

[0264] <Other Ingredients>

[0265] This composition may contain ingredients other than those described above (hereinafter also referred to as "other ingredients").

[0266] Other components include dispersants, catalysts, and curing accelerators (e.g., the curing accelerators described in Japanese Patent Application Publication No. 2023-125309).

[0267] When the composition contains other ingredients, it is preferred that the content of the other ingredients is 1 to 0.001% by mass relative to the total mass of the composition, more preferably 0.5 to 0.005% by mass, and even more preferably 0.1 to 0.01% by mass.

[0268] The concentration of solid components in this composition is preferably 20-60% by mass, more preferably 25-55% by mass, and even more preferably 30-50% by mass.

[0269] As long as the solid content concentration of this composition is 20% by mass or more, the surface exposure rate of the metal nanowires can be easily set within the above-mentioned range. Furthermore, as long as the solid content concentration of this composition is 60% by mass or less, the operability of this composition is excellent.

[0270] The term "solid component" in this composition refers to the component that forms the film formed using this composition. Typically, it refers to all components other than the solvent. Furthermore, liquid components are also considered solid components as long as they form a film.

[0271] The viscosity of this composition at 25°C is 100 mPa·s or less, preferably 90 mPa·s or less, and more preferably 80 mPa·s or less. As long as the viscosity is 100 mPa·s or less, the pores created by the evaporation of the solvent during the drying process are easily embedded by the thermosetting compound and other components. Therefore, the formation of pores in the obtained sheet can be further suppressed, thus improving the effectiveness of the present invention.

[0272] From the viewpoint of appropriate film thickness, it is preferable that the lower limit of the viscosity of this composition at 25°C is 5 mPa·s or more, more preferably 10 mPa·s or more, and even more preferably 20 mPa·s or more.

[0273] The viscosity of this composition was measured using an E-type viscometer at 25°C.

[0274] There is no particular limitation on the manufacturing method of this composition; methods for mixing the above-mentioned components by known methods can be listed.

[0275] [Drying process]

[0276] The drying process is a process of obtaining a sheet by drying the composition. The solvent in the composition evaporates during the drying process. Furthermore, the drying temperature of the composition in the drying process is lower than the curing temperature of the thermosetting compound, therefore the thermosetting compound will not cure due to the drying process.

[0277] The drying process can be used to dry the coating obtained by applying the composition, or to dry the composition flowing into a container such as a mold.

[0278] There are no particular limitations on the method of coating this composition, but examples include printing, spraying, roller coating, bar coating, curtain coating, spin coating, and stencil coating (slit coating).

[0279] When the drying temperature of this composition in the drying process is set to T, the curing temperature of the aforementioned thermosetting compound is set to Tx, and the boiling point of the aforementioned solvent is set to Ty, the value of subtracting T from Tx (Tx-T) is 10°C or more, and the value of subtracting T from Ty (Ty-T) is -60°C or more. By satisfying these drying conditions, the solvent evaporates slowly, and therefore the pores created by the evaporation of the solvent are easily embedded by components such as the thermosetting compound. As a result, the porosity of this sheet material can be reduced.

[0280] In addition, when there are two or more solvents, the boiling point of the solvent with the highest boiling point is used as the boiling point Ty.

[0281] From the viewpoint of further reducing the porosity of the sheet material, a temperature Tx-T of 10°C or higher is preferred, and 40°C or higher is more preferably 70°C or higher. From the viewpoint of drying efficiency, a maximum Tx-T of 220°C or lower is preferred, 190°C or lower is more preferably 160°C or lower.

[0282] Ty-T is -60°C or higher. From the viewpoint of further reducing the porosity of the sheet, it is preferably 0°C or higher, more preferably 20°C or higher. From the viewpoint of drying efficiency, it is preferably the upper limit of Ty-T is 60°C or lower, more preferably 50°C or lower, and even more preferably 40°C or lower.

[0283] The drying temperature T is preferably 30 to 130°C, more preferably 40 to 100°C, and even more preferably 50 to 80°C.

[0284] The preferred ranges for the curing temperature Tx of the thermosetting compound and the preferred ranges for the boiling point Ty of the solvent are as described above.

[0285] The drying time in the drying process is preferably 1 to 40 minutes, more preferably 5 to 20 minutes.

[0286] The sheet obtained after the drying process is preferably in stage B. Stage B is as described above.

[0287] [Pressing process]

[0288] This manufacturing method may include a pressing process that applies pressure to the sheet after the drying process. By including the pressing process, the porosity of the sheet can be further reduced, thereby further reducing the porosity of the sheet.

[0289] The pressure during the pressing process is preferably 5 to 70 MPa, more preferably 20 to 50 MPa.

[0290] The pressing process can be accompanied by heat treatment, preferably at a temperature lower than the curing temperature Tx of the thermosetting compound. Specifically, the heat treatment temperature is preferably below 130°C, more preferably below 100°C, and preferably above 30°C, more preferably above 40°C.

[0291] The pressurization process can be carried out under either atmospheric pressure or depressurization.

[0292] Pressing machines used in the pressure process include, for example, flatbed presses and roller presses.

[0293] The sheet obtained after the pressing process is preferably in state B. Regarding state B, as described above.

[0294] Example

[0295] The present invention will now be described in further detail with reference to embodiments. The materials, amounts, proportions, processing contents, and processing order shown in the following embodiments can be appropriately modified without departing from the spirit of the invention. However, the scope of the invention should not be limited by the embodiments shown below.

[0296] [Fabrication of Metal Nanowire 1]

[0297] <Fabrication of Aluminum Substrate>

[0298] Molten metal was prepared using an aluminum alloy containing 0.06% by mass of Si, 0.30% by mass of Fe, 0.005% by mass of Cu, 0.001% by mass of Mn, 0.001% by mass of Mg, 0.001% by mass of Zn, and 0.03% by mass of Ti, with the remainder being Al and unavoidable impurities. After molten metal treatment and filtration, an ingot with a thickness of 500 mm and a width of 1200 mm was produced by DC (Direct Chill) casting.

[0299] Next, the surface is scraped off with an average thickness of 10mm using a surface scraper, and then kept at 550°C for about 5 hours. When the temperature drops to 400°C, a 2.7mm thick rolled plate is obtained using a hot rolling mill.

[0300] Furthermore, after heat treatment at 500°C using a continuous annealing machine, the aluminum substrate is finished to a thickness of 1.0 mm by cold rolling to obtain JIS (Japanese Industrial Standard) 1050 material.

[0301] After the aluminum substrate was formed into a wafer with a diameter of 200 mm (8 inches), the following processes were performed.

[0302] <Electrolytic grinding treatment>

[0303] The aluminum substrate was subjected to electrolytic polishing treatment using an electrolytic polishing slurry with the following composition under conditions of 25V voltage, 65℃ liquid temperature, and 3.0m / min liquid flow rate.

[0304] The cathode was a carbon electrode, and the power supply used was a GP0110-30R (manufactured by Takasago Manufacturing Co., Ltd.). Furthermore, the electrolyte flow rate was measured using a vortex flow meter FLM22-10PCW (manufactured by AS ONE Co., Ltd.).

[0305] (Composition of electrolytic grinding fluid)

[0306] • 85% phosphoric acid (prepared by Wako Pure Chemical, Ltd.) 660mL

[0307] 160mL of pure water

[0308] 150 mL of sulfuric acid

[0309] 30 mL of ethylene glycol

[0310] <Anodizing Process>

[0311] Next, the aluminum substrate after electrolytic polishing was subjected to anodizing treatment based on the self-ordering method according to the steps described in Japanese Patent Application Publication No. 2007-204802.

[0312] The aluminum substrate after electrolytic grinding was subjected to pre-anodization treatment for 5 hours using an electrolyte of 0.50 mol / L oxalic acid at a voltage of 40V, a liquid temperature of 16℃, and a liquid flow rate of 3.0 m / min.

[0313] Subsequently, a demolding process was carried out by immersing the pre-anodized aluminum substrate in a mixed aqueous solution of 0.2 mol / L chromic anhydride and 0.6 mol / L phosphoric acid (liquid temperature: 50℃) for 12 hours.

[0314] Subsequently, an anodized film with a thickness of 40 μm was obtained by performing a re-anodization treatment for 5 hours using an electrolyte of 0.50 mol / L oxalic acid at a voltage of 40 V, a liquid temperature of 16 °C, and a liquid flow rate of 3.0 m / min.

[0315] Furthermore, in both the pre-anodizing and re-anodizing processes, stainless steel electrodes were used as cathodes, and the power supply was a GP0110-30R (manufactured by Takasago Manufacturing Co., Ltd.). The cooling device used was a NeoCool BD36 (manufactured by YamatoScientific Co., Ltd.), and the stirring and heating device used a paired stirrer PS-100 (manufactured by EYELA TOKYORIKAKIKAI CO.,LTD.). In addition, the electrolyte flow rate was measured using a vortex flow meter FLM22-10PCW (manufactured by AS ONE Co., Ltd.).

[0316] <Metal Filling Process>

[0317] Next, an electroplating process was performed using an aluminum substrate as the cathode and platinum as the positive electrode.

[0318] Specifically, a metal-filled microstructure with copper filling the porous (micropore) interior is produced by constant current electrolysis using a copper plating solution with the composition shown below.

[0319] Here, constant current electrolysis was performed using a plating apparatus manufactured by Yamamoto Gold Plating Tester Co., Ltd., and a power supply (HZ-3000) manufactured by Hokuto Electric Co., Ltd. was used. After confirming the deposition potential in the plating solution by cyclic voltammetry, the treatment was carried out under the conditions shown below.

[0320] (Composition and conditions of copper plating solution)

[0321] Copper sulfate 100g / L

[0322] · Sulfuric acid 50g / L

[0323] · Hydrochloric acid 15g / L

[0324] Temperature 25℃

[0325] • Current density 10A / dm 2

[0326] The surface of the anodic oxide film after filling the pores with metal was observed using FE-SEM. The sealing rate (number of sealed pores / 1000 pores) was calculated by observing whether there were metal-based sealing pores in 1000 pores, and the result was 96%.

[0327] Furthermore, the anodic oxide film after filling the pores with metal was machined in the thickness direction using FIB, and its cross-section was photographed using FE-SEM (magnification of 50,000) to confirm the interior of the pores. The results showed that the filling height from the bottom of the sealed pores was 35 μm.

[0328] <Separation Process>

[0329] The filled metal was separated from the anodic oxide film and the aluminum substrate by immersion in an aqueous solution of potassium hydroxide (concentration: 5 mol / L) at 60°C for 300 seconds, thus obtaining a separated metal. Specifically, the anodic oxide film was dissolved by immersion in the aqueous solution of potassium hydroxide (concentration: 5 mol / L) at 60°C for 300 seconds, and the filled metal was separated by peeling off the aluminum substrate simultaneously with the dissolution of the anodic oxide film (after 300 seconds).

[0330] <Drying Process>

[0331] Next, the separated metal was recovered by suction filtration using a membrane (0.4μm, PTFE, manufactured by Omnipore) and then dried.

[0332] <Reduction or Removal Process>

[0333] Next, the separated metal recovered on the membrane was immersed in an aqueous solution containing 1% citric acid for 3 hours at room temperature (23°C, the same below).

[0334] Subsequently, the separated metal on the membrane was recovered.

[0335] <Pulverizing Process>

[0336] Next, 1% by mass of the recovered separated metal was added to the water, and a cavitation-based pulverization process (pressure: 50 MPa) was carried out using a Star Burst Mini manufactured by SUGINO MACHINE LIMITED.

[0337] Subsequently, the separated metals, which had undergone pulverization, were recovered by suction filtration using a membrane (0.4 μm, PTFE, manufactured by Omnipore) and dried under reduced pressure at 50 °C for 12 hours, thereby producing metal nanowires 1.

[0338] [Fabrication of Metal Nanowires 2]

[0339] The aforementioned “reduction or removal process” was not performed; otherwise, metal nanowires 2 were obtained in the same manner as the manufacture of metal nanowires 1.

[0340] [Example 1]

[0341] <Preparation of the Composition>

[0342] 19g of epoxy compound 1 (EPICLON EXA-830LVP, manufactured by DIC Corporation, thermosetting compound, molecular weight: 310), 9g of phenolic compound 1 (BIR-PC, manufactured by Asahi Organics Co., Ltd., thermosetting compound, molecular weight: 352), 0.1g of silane coupling agent (KBM-403, manufactured by Shin-Etsu Silicone Co., Ltd., silane coupling agent with epoxy groups), and 18g of methyl ethyl ketone (MEK, boiling point Ty: 79.64℃) were added to a container and stirred at room temperature for 3 hours to obtain mixture A. Furthermore, the curing temperature Tx of the above composition was determined by DSC to be 140℃.

[0343] Metal nanowires 2, mixture A, and MEK were added to a container and stirred at room temperature for 1 hour to obtain composition A. At this time, the amount of each component added was adjusted so that the solid component concentration (mass%) of composition A was 42% by mass, and the content of metal nanowires 2 relative to the total content of metal nanowires 2 and thermosetting compounds was 90% by mass.

[0344] In addition, the viscosity of composition A at 25°C, as measured using an E-type viscometer, was 50 mPa·s.

[0345] <Sheet Manufacturing>

[0346] At room temperature and atmospheric conditions, after the composition A is poured into a silicone rubber mold, it is dried in an explosion-proof oven with the exhaust connected to the mold into which the composition A enters, at atmospheric conditions and 130°C (drying temperature T) for 30 minutes to allow MEK to evaporate (drying process).

[0347] After the drying process, the mold was removed, and a sheet was obtained. Under atmospheric conditions, the sheet was pressed using a press at 50°C and 40MPa (pressing process) to obtain sheet 1 of Example 1 (thickness: 100μm).

[0348] [Examples 2-4]

[0349] The drying temperature T in the drying process was set as shown in Table 1. Otherwise, the sheets 2 to 4 of Examples 2 to 4 (all with a thickness of 102 μm) were obtained in the same manner as the sheet of Example 1.

[0350] [Examples 5-6]

[0351] Metal nanowire 1 was used instead of metal nanowire 2, and composition B was otherwise obtained in the same manner as the composition of Example 1. Furthermore, the viscosity of composition B at 25°C, measured using an E-type viscometer, was 51 mPa·s.

[0352] Instead of composition A, composition B was used, and the drying temperature T in the drying process was set as described in Table 1. Otherwise, the sheets 5 to 6 of Examples 5 and 6 (all with a thickness of 101 μm) were obtained in the same manner as the sheet of Example 1.

[0353] [Examples 7-8]

[0354] The concentration of the solid components in the composition was adjusted as shown in Table 1. Otherwise, composition C was obtained in the same manner as the composition of Example 1. Furthermore, the viscosity of composition C at 25°C, measured using an E-type viscometer, was 28 mPa·s.

[0355] Instead of composition A, composition C was used, and the drying temperature T in the drying process was set as described in Table 1. Otherwise, the sheets 7-8 of Examples 7-8 (all with a thickness of 95 μm) were obtained in the same manner as the sheet of Example 1.

[0356] [Examples 9-11]

[0357] Instead of composition A, composition B was used, and the drying temperature T in the drying process was set as described in Table 1. Otherwise, the sheets 9 to 11 of Examples 9 to 11 (all with a thickness of 101 μm) were obtained in the same manner as the sheet of Example 1.

[0358] [Comparative Examples 1-3]

[0359] Instead of epoxy compound 1, epoxy compound 2 (EPICLON (registered trademark) 830, manufactured by DIC Corporation, thermosetting compound) was used. Otherwise, composition D was obtained in the same manner as the composition of Example 1. Furthermore, the curing temperature Tx of the above composition was determined to be 145°C by DSC. And, the viscosity of composition D at 25°C, measured using an E-type viscometer, was 108 mPa·s.

[0360] Instead of composition A, composition D was used, and the drying temperature T in the drying process was set as described in Table 1. Otherwise, comparative examples 1 to 3 (all with a thickness of 116 μm) were obtained in the same manner as the sheet of Example 1.

[0361] Porosity

[0362] The porosity of sheets 1-11 and H1-H3 was determined using the following method.

[0363] The sheets were cut along their thickness. After platinum-clad cross-sections of the exposed sheets were processed using focused ion beam (FIB) machining. Subsequently, field emission scanning electron microscopy (FE-SEM) (Thermo Fisher Scientific Inc.) was used to image the cross-sections of the sheets at 10 different fields of view, with an accelerating voltage of 2 kV and a magnification of 1000x. Furthermore, the pores appear as black in the images.

[0364] The captured image was binarized using the image processing software "ImageJ" to separate the image into dark and bright areas, thus obtaining image processing data. In the binarized image processing data, the dark areas correspond to the pores of the sheet material, while the bright areas correspond to the parts other than the pores (metal nanowires and thermosetting compounds).

[0365] Based on the binarized image processing data, the area of ​​the dark areas is automatically detected, and the area of ​​the pores and the area of ​​the parts other than the pores (the bright areas) are calculated based on the obtained measurements. The porosity is calculated for each image processing data point according to the following formula. The arithmetic mean of the 10 values ​​thus calculated is taken as the porosity (%) of the sheet. The results are shown in Table 1.

[0366] Porosity (%) = 100 × [Area of ​​pores / (Area of ​​pores + Area of ​​the portion excluding pores)]

[0367] [Oxidation Rate]

[0368] The oxidation rate of the metal nanowires contained in sheets 1-11 and H1-H3 was determined by the following method.

[0369] The surface of each sheet was analyzed using an X-ray diffraction apparatus (manufactured by Rigaku Corporation) under conditions of 40 kV and 30 mA from a Cu ray source, and diffraction patterns were obtained.

[0370] Regarding the obtained diffraction pattern, using the Inorganic Crystal Structure Database (ICSD), based on the identification of the main peaks of MOx and M (where M represents metal atoms and x represents integers), the area of ​​the peaks originating from the metal and the percentage of the area of ​​the peaks originating from the metal oxide were calculated, and the oxidation rate of the metal nanowire was calculated according to the following formula. The results are shown in Table 1.

[0371] Oxidation rate (%) = 100 × [Area of ​​peaks originating from metal oxides / Area of ​​peaks originating from metal]

[0372] For example, when M (metal atom) is Cu, based on the identification of the following main peak values, the ratio of the peak area of ​​Cu2O to the peak area of ​​CuO (i.e., oxidation rate, in %) was calculated.

[0373] The main peak of Cu2O is around 2θ=37°.

[0374] The main peak of CuO is around 2θ=39°.

[0375] The main peak of Cu is around 2θ=43°.

[0376] [Surface Exposure Rate]

[0377] The surface exposure rate of metal nanowires in sheets 1-11 and H1-H3 was determined by the following method.

[0378] Using an optical microscope (manufactured by KEYENCE CORPORATION), images were captured at 100x magnification for observation of the surface of each sheet at 10 different fields of view. Furthermore, due to the high density of the metal nanowires, they appear white when exposed on the surface in the captured images.

[0379] The captured image was binarized using the image processing software "ImageJ" to separate the image into dark and bright areas, thus obtaining image processing data. In the binarized image processing data, the bright areas correspond to the metal nanowires exposed on the sheet surface, while the dark areas correspond to the parts other than the metal nanowires exposed on the sheet surface (thermosetting compounds and metal nanowires embedded in thermosetting compounds).

[0380] Based on the binarized image processing data, the area of ​​the exposed portion is automatically detected and measured. The area of ​​the metal nanowires exposed from the sheet surface and the area of ​​the portion excluding the exposed metal nanowires are calculated based on the obtained measurements. The surface exposure rate is calculated for each image processing data point according to the following formula. The arithmetic mean of the 10 values ​​thus calculated is taken as the surface exposure rate (%) of the metal nanowires in each sheet. The results are shown in Table 1.

[0381] Surface exposure rate (%) = 100 × [Area of ​​metal nanowires exposed from the sheet surface / (Area of ​​metal nanowires exposed from the sheet surface + Area of ​​the portion excluding metal nanowires exposed from the sheet surface)]

[0382] [Content of metal nanowires]

[0383] The content (volume %) of metal nanowires is calculated from the amount of each component loaded during sheet manufacturing.

[0384] Specifically, the volume of each component (solid component) in the sheet is calculated by dividing the weight of each component used in manufacturing the sheet by its theoretical specific gravity. Then, the volume occupied by the metal nanowires is divided by the sum of the volumes of all components (solid components) in the sheet to calculate the content of the metal nanowires (volume %).

[0385] [Relative thermal conductivity]

[0386] In a nitrogen atmosphere, hot pressing of sheets 1 to 11 and H1 to H3 was performed using a press at 180°C and 10MPa.

[0387] The thermal conductivity of each sheet (thermally conductive sheet) after hot pressing was calculated according to the following formula. Regarding the results, the thermal conductivity value of the thermally conductive sheet in Comparative Example 1 was converted to "1.0" and expressed as a ratio (relative thermal conductivity). The results are shown in Table 1.

[0388] Thermal conductivity (W / m·K) = Specific gravity (g / cm³) 3 ) × specific heat (kJ / kg·K) × thermal diffusivity (mm) 2 / s)

[0389] Here, the specific gravity was determined by the Archimedes method, the specific heat was calculated by differential scanning calorimetry (DSC), and the thermal diffusivity was determined by the laser flash method.

[0390] Furthermore, regarding the sheets 9 to 11 of Examples 9 to 11, the porosity, oxidation rate, and surface exposure rate were determined using the hot-pressed sheets (thermally conductive sheets) used in the thermal conductivity measurement, and the methods described above were applied. The results are shown in Table 1.

[0391] [Table 1]

[0392] As shown in Table 1, it is evident that for sheets with a porosity of 20.0% or less, the thermal conductivity of the obtained thermally conductive sheets is excellent when hot-pressed at a temperature above the curing temperature of the thermosetting compound (Examples 1-11). On the other hand, it is evident that for sheets with a porosity exceeding 20.0%, the thermal conductivity of the obtained thermally conductive sheets is poor when hot-pressed at a temperature above the curing temperature of the thermosetting compound (Comparative Examples 1-3).

[0393] The comparison between Examples 3 and 5 and between Examples 4 and 6 shows that the thermal conductivity of the obtained thermally conductive sheet is superior when a sheet containing metal nanowires with low oxidation rate is used.

[0394] The comparison between Examples 3 and 7 and between Examples 4 and 8 shows that the thermal conductivity of the obtained thermally conductive sheet is superior when a sheet with a high surface exposure rate of metal nanowires is used.

[0395] Symbol Explanation

[0396] 1-Valve metal substrate, 2-Porous (microporous), 3-Anodized film, 4-Metal, 5-Separated metal, 10-Metal nanowire.

Claims

1. A sheet comprising metal nanowires and a thermosetting compound, wherein, The porosity of the sheet is below 20.0%.

2. The sheet according to claim 1, wherein, The oxidation rate of the metal nanowires is less than 5.0%.

3. The sheet according to claim 1 or 2, wherein, The surface exposure rate of the metal nanowires is above 20.0%.

4. The sheet according to claim 1 or 2, wherein, The metal constituting the metal nanowires is copper.

5. The sheet according to claim 1 or 2, wherein, The content of the metal nanowires is 30 to 80% of the total volume of the sheet.

6. The sheet according to claim 1 or 2, wherein, The thickness of the sheet is 20–200 μm.

7. The sheet according to claim 1 or 2, wherein, The thermosetting compound includes epoxy compounds and phenolic compounds.

8. The sheet according to claim 1 or 2, wherein, The thermosetting compound has a molecular weight of less than 1000.

9. A method for manufacturing a sheet material, comprising: The process of drying a composition containing metal nanowires, thermosetting compounds, and solvents to obtain a sheet. The composition has a viscosity of less than 100 mPa·s at 25°C. When the drying temperature of the composition is set to T, the curing temperature of the thermosetting compound is set to Tx, and the boiling point of the solvent is set to Ty, The difference between Tx and T is 10°C or more. The difference between Ty and T is greater than -60°C.

Citation Information

Patent Citations

  • Lubricating device of internal combustion engine

    JP1991100311A

  • Method of manufacturing structure

    JP2007204802A

  • Anisotropic conductive member, and its manufacturing method

    JP2008270158A

  • Heat conductive sheet, and laminate

    JP2023125309A